PENGALAMAN PENGGUNA, KEAMANAN TRANSAKSI, KEMUDAHAN PENGGUNAAN, KENYAMANAN, DAN PENGARUHNYA TERHADAP PERILAKU PEMBELIAN ONLINE SECARA IMPULSIF - Didit Darmawan; Arif Rachman Putra (RELASI : JURNAL EKONOMI, 2022)
In Indonesia, online shopping has become a trend and transactions have increased drastically, marked by the development of business players involved in the online marketplace industry, one of which is Lazada, which is the top marketplace in Indonesia. Lazada is an online product buying and selling application that offers a variety of products and uses the internet and social media as a forum for interactive two-way interactions with its users. Product bids, attractive prices and availability of information can lead to impulsive buying behavior. The impulse to buy impulsively is described as a complex, sudden, pleasant purchase and the decision-making process occurs instantaneously without thinking of any other considerations. This study has the main objective of identifying the effect of user experience, transaction security, ease of use, convenience on impulsive online buying behavior aimed at the Lazada marketplace. The population in this study are consumers who have made online purchases at Lazada. The sampling technique used is non-probability sampling, with a purposive sampling method with the following sample criteria: consumers who have made online Lazada purchases more than once, and aged over 17 years to 50 years. Respondents came from the city of Sidoarjo and totaled 120 people. Multiple linear regression analysis is an analytical tool used in this study. The t test is to prove the research hypothesis which previously carried out the reliability test. From the results of the analysis of the research results, it is found that experience, safety, convenience and comfort have a significant influence on impulsive buying behavior at Lazada. The experience variable is a variable that has a dominant effect. Keywords: experience, security, ease of use, enjoyment, impulsive buying behavior.